Effects of Fusarium Mycotoxin Exposure on Lipid Peroxidation and Glutathione Redox System in the Liver of Laying Hens - Szabina Kulcsár; Benjámin Kövesi; Krisztián Balogh; Erika Zándoki; Zsolt Ancsin; Balláné Erdélyi Márta; Miklós Mézes (MDPI AG, 2021)
It has been proven by several studies that Fusarium mycotoxins induce oxidative stress in animals, consequently inducing lipid peroxidation, which the glutathione system can neutralize. A short-term (3-day) in vivo feeding trial was performed with laying hens using a double dose of the EU recommendation for mycotoxin contamination (T-2 toxin 0.5 mg/kg feed; deoxynivalenol (DON) 10 mg/kg feed; fumonisin B1 (FB1) 40 mg/kg feed). Some lipid peroxidation and glutathione redox system parameters and gene expression levels were measured in the liver. The results show that FB1 significantly decreased the reduced glutathione (GSH) content and the activity of glutathione peroxidase (GPx) compared to the control and the two other mycotoxin-treated groups on day 3. Lipid peroxidation was affected by all three mycotoxins. Significantly lower values were observed in the case of conjugated dienes for all of the three mycotoxins and malondialdehyde concentration as an effect of DON on day 3. T-2 toxin and DON upregulated the expression of the GPX4 gene. The results show that Fusarium mycotoxins had different effects at the end of the trial. The FB1 exposure caused a decrease in the glutathione redox markers, while DON decreased the formation of malondialdehyde. The results suggest that the Fusarium mycotoxins investigated individually differently activated the antioxidant defense and caused low-level oxidative stress at the dose applied.